Efikasi Ekstrak Sirih, Rimpang Lengkuas dan Kunyit terhadap Penekanan Pertumbuhan Xanthomonas oryzae - Rini Laraswati; Umi Kulsum; Evan Purnama Ramdan (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2021)
One of the important diseases in rice is the Bacterial Leaf Blight (HDB) or the so-called kresek disease caused by Xanthomonas oryzae pv. oryzae. This disease is one of the main diseases of rice in Indonesia. This is supported by agricultural conditions in hot and humid tropical areas so that disease development is more optimal. The purpose of this study was to determine the efficacy of betel leaf extract and some rhizomes in suppressing the growth of Xanthomonas oryzae pv. oryzae in-vitro scale. The research was conducted at the Center for Forecasting Plant Pest Organisms (BBPOPT), Karawang, West Java. The extracts of galangal, turmeric, and betel were prepared at concentrations of 10, 15, and 25%, the method used was a scatter plate by taking 10, 50, and 100 μL of Xoo isolate liquid, holding the petri dish to a bunsen fire, and spraying Xoo isolates liquid. into a petri dish containing PSA media + rhizome extract, the dispersing tool used is drigalski. The results of daily observations of rhizome extract antagonist testing on Xoo growth showed that the treatment of betel leaf extract with a concentration of 10%, 15%, and 25% had a high bacterial inhibitory value compared to other treatments with 100% inhibition, whereas in the control treatment (only PSA media) shows that it does not have bacterial inhibition, and the galangal rhizome extract treatment has the highest inhibitory power when compared to other treatments on 100 μL of Xoo bacterial suppression.